Analisis Konsentrasi Total Suspended Particular (TSP) pada Udara Ambien di Ruas Jalan Pangeran Diponegoro Kota Kendari - Putra, Adi; Ilham, Ilham; Sumarlin, Sumarlin (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Air pollution is one of the problems faced by both developing and developed countries. more than 90% of people in developing countries live in environments with ambient air conditions that are unhealthy to breathe. The increasing number of two-wheeled and four-wheeled vehicles from year to year triggers congestion and causes air pollution, one of the roads that is crowded with two- and four-wheeled vehicles in Kendari City, namely Pangeran Diponegoro street. This study aims to determine the concentration of total suspended particulate (TSP) on Pangeran Diponegoro street, Kendari City and the amount of traffic volume at an interval of three measurements in one day at a predetermined location. The results obtained are the concentration of Total Suspended Particulate in ambient air at Jalan Pangeran Diponegoro, Kendari City within an interval of three measurements in one day, namely at 08.30-09.30 WITA, at 11.30-12.30 WITA, and at 14.30-15.30 WITA. laboratory test results obtained in the morning at 28°C, during the day the results were obtained with a temperature of 32°C, and in the afternoon the results were obtained with a temperature of 29°C which still meets the PP RI standard No. 22 of 2001 and the results of calculating the volume of vehicles in three intervals, namely in the morning at 08.30-09.30 WITA, the number of vehicles is 1480 units/hour, in the afternoon at 11.30-12.30 WITA, 1284 units/hour are obtained, and in the afternoon at 11.30-12.30 WITA. at 14.30-15.30 WITA with the number of vehicles as much as 1523 units/hour.